PENGARUH KUALITAS AUDIT DAN LEVERAGE TERHADAP PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) TAHUN 2016 - Camelia Verahastuti, Gitaraya Datutasik Elfreda Aplonia Lau (EKONOMIA, 2017)
The financial statements are a very important measuring tool for assessing the performance of a company's profit-generating management. For that the company performs various ways including earnings management practices for a particular interest. Audit quality and leverage each have an important role in the practice of earnings management where audit quality affects the accuracy of earnings in a company's financial statements and the high level of leverage becomes one of the factors of earnings management. The purpose of this study is to determine the effect of audit quality and leverage on earnings management practices at manufacturing companies in Indonesia Stock Exchange Year 2016. Theoretical basis in this study is management accounting that focuses on ratios. The hypothesis proposed is the effect of audit quality and leverage on earnings management practices of manufacturing companies. Analyzer used in this research is multiple regression analysis with significance 0,050 and data analysis using spss application. The variable for audit quality is measured using the size of Public Accounting Firm (KAP) that is big four and non big four, leverage is proxyed by Debt to Asset Ratio (DAR) ratio with total debt divided by total asset while earning management is measured from discretionary accruals model Jones Modification . Sampling method used is by purposive sampling method. The results of this research indicate that audit quality has an insignificant influence and has a negative effect to earnings management, while leverage also has an insignificant effect and has a negative effect. The conclusion of this study states that both hypotheses have been accepted, which means the quality of audit and leverage have no significant effect and have a negative effect on earnings management.